Effect of Soil on Refinery Buried Cooling Water Pipe - Afan, Kareem B.; Noaman, Riyadh M.; Shnaihj, Kareem T.; Asli, Hussam A.; majeed, Aqbal A.; Ali, Najwa S. (Journal of Petroleum Research and Studies, 2017)
This work is focused to investigate soil parameters (resistivity, PH, sulfate, moisture) that affect the corrosive nature of soil toward the buried cooling water pipe carbon steel used to supply the water to refinery units and the work include on line survey of this unprotected pipe to measuring the potential at each unit of refinery to evaluate the pipe coating. The soil resistivity measuring at two depth (2&4) meter at many sites, it is found that the soil resistivity at the depth (2) meter (pipe depth) either slightly corrosive or moderately corrosive and other soil parameters were measured at summer and winter seasons, found they change seasonally. The average pipe potential at each unit of refinery is around (-410mV) and that is mean the carbon steel pipe coating is poor.